PENGARUH SUPLEMENTASI Portulaca oleracea DENGAN LEVEL YANG BERBEDA TERHADAP KADAR TRIGLISERIDA DAN HDL (High Density Lippoprotein) SERUM DARAH KAMBING JAWARANDU (Capra aegagrus hircus) - Fitra Taufiqul Hakim; Liman Liman; Sri Suharyati; Erwanto Erwanto (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
This study aimed to determine the effect of supplementation of Portulaca oleracea with different levels of triglycerides and High-Density Lipoprotein (HDL) content of blood serum. This research was conducted in February-March 2021 in the village of Rejo Asri, Seputih Raman District, Central Lampung Regency, Lampung Province. Examination of white blood cells, and white blood cell differential was carried out at the Veterinary Center of Lampung Province. The experimental design used was a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments were basal ration (P0), basal ration with 5% Portulaca oleracea supplementation (P1), basal ration with 10% Portulaca oleracea supplementation (P2), and basal ration with 15% Portulaca oleracea supplementation (P3). The data obtained were analyzed with analysis of variance with a significance level of 5%. The results showed that Jawarandu goats fed with purslane flour with different levels showed no significantly different results (P> 0.05) which had an average of triglyceride levels of 80.2 ± 5.26 mg/dL (P0), 79.6± 5.46 mg/dL (P1), 92±10.89 mg/dL (P2), and 81.2± 7.38 mg/dL (P3), while for HDL, those were 36.4±5.41 mg/dL (P0), 33.8±4.93 mg/dL (P1), 38.5±3.05 mg/dL (P2), and 31.3± 4.74 mg/dL (P3) which were in the normal range. Keywords: HDL, Jawarandu Goat, Portulaca oleracea, Triglycerides